On Foot in the Pennines - Smith, Roland, 1944-; With Photographs by Cleare, John (Newton Abbot David & Charles, 1994)
From the misty peaks of Derbyshire to the craggy heart of the Cheviots, the Pennines offer a wonderful diversity of prime walking country. For all walkers who love to explore these areas, author and walker Roland Smith presents 38 magnificent routes, promising many enjoyable days in this area
Include Color Illustration, Bibliography and Index
Keywords: Walking -- England--Pennine Chain